IMPACTS OF FUNGICIDES ON BIOCHEMICAL, HAEMATOLOGICAL, HISTOPATHOLOGICAL, DEVELOPMENT, REPRODUCTION, OXIDATIVE STRESS AND BEHAVIORAL ASPECTS: A REVIEW - SOMAN, SHALU; ARUN, A. U. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Pesticides, insecticides, herbicides and fungicides are being used by farmers all over the world in order to increase their food production. Apart from agriculture, fungicides also used to treat fungal infections in case of animals. Release of these fungicides from agriculture and related areas can reach nearby water bodies, which in turn can affect aquatic fauna. The present review highlighted the ill effects of fungicides on biochemical, haematological, histopathological, development, reproduction and behavior on different life forms. Exposure to fungicides resulted in an elevated levels of plasma enzymes, serum transaminases and glucose with reduction in level of protein. Red blood cell count, white blood cell count, haemoglobin, packed cell volume, mean corpuscular volume, mean corpuscular haemoglobin concentration and mean corpuscular haemoglobin values were affected. Fungicides resulted in severe abnormalities on gills, liver and kidney of test species. It also affected reproduction and induced various malformations during development. It also led to the formation of reactive oxygen species, which resulted in oxidative stress. Alterations of these parameters can be used as potential biomarkers to evaluate the potential ecotoxicity of fungicide to organisms. Therefore, we should take stringent measures to minimize the use of these fungicides on agriculture and other purposes.